2010
DOI: 10.1007/s00464-010-1133-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of laparoscopic left lateral sectionectomy without the Pringle maneuver: through resection of benign and malignant tumors to living liver donation

Abstract: BackgroundLaparoscopic left lateral sectionectomy (LLS) has gained popularity in its use for benign and malignant tumors. This report describes the evolution of the authors’ experience using laparoscopic LLS for different indications including living liver donation.MethodsBetween January 2004 and January 2009, 37 consecutive patients underwent laparoscopic LLS for benign, primary, and metastatic liver diseases, and for one case of living liver donation. Resection of malignant tumors was indicated for 19 (51%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Even if patient satisfaction should always be a major goal of surgery, in oncological surgery cosmesis has been traditionally considered a secondary priority so that application of laparoscopic techniques are accepted mainly for other advantages (i.e., faster recovery, lower immunosuppressive effect, better postoperative performance status for adjuvant chemotherapy). However, in liver surgery cosmesis may be a point of significant importance in some subsets of patients, including living donors of left-lateral sector and resections for benign diseases (i.e., adenomas, giant hemangioma of the left lobe) [24]. Indeed, the present study included some benign cases in both groups, even if the grade of patient satisfaction was not specifically addressed.…”
Section: Discussionmentioning
confidence: 95%
“…Even if patient satisfaction should always be a major goal of surgery, in oncological surgery cosmesis has been traditionally considered a secondary priority so that application of laparoscopic techniques are accepted mainly for other advantages (i.e., faster recovery, lower immunosuppressive effect, better postoperative performance status for adjuvant chemotherapy). However, in liver surgery cosmesis may be a point of significant importance in some subsets of patients, including living donors of left-lateral sector and resections for benign diseases (i.e., adenomas, giant hemangioma of the left lobe) [24]. Indeed, the present study included some benign cases in both groups, even if the grade of patient satisfaction was not specifically addressed.…”
Section: Discussionmentioning
confidence: 95%
“…Studies from other centers showed similar advantages (7)(8)(9)(10)(11). In the western literature, indication of liver resection was greatly governed by the Barcelona Clinic Liver Cancer classification (12).…”
Section: Am Writing In Response To Professor Taizo Hibi's Editorialmentioning
confidence: 82%
“…To date, only a few papers have focused on this issue, mainly examining conversion rates (CRs) and blood loss. [ 1117 ] However, it is difficult to draw final conclusions because many factors influence LC outcomes, such as the center and team experience, pathology referral, and individual surgical skills, allowing for the reproducibility of open techniques with the laparoscopic approach. Accordingly, the LC for laparoscopic minor hepatectomy is believed to be roughly completed after 60 procedures, allowing for the best performances in terms of conversion rates [15] …”
Section: Introductionmentioning
confidence: 99%